Autoimmune polyglandular syndrome type 2 in an 15-year-old boy - Badeński, Andrzej; Badeńska, Marta; Mierzwa, Magdalena; Stojewska, Małgorzata; Deja, Grażyna; Szczepańska, Maria; Ziora, Katarzyna (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Autoimmune polyendocrine syndromes (APS) include a diverse group of clinical conditions, characterized by functional impairment of many endocrine glands. Type 2 APS is characterized by the mandatory presence of Addison’s disease, which may be associated with either autoimmune thyroid diseases as a Schmidt’s syndrome or type 1 diabetes mellitus as a Carpenter syndrome. The described patient with well-controlled diabetes mellitus type 1, presented with sudden, frequent episodes of hypoglycemia, daytime somnolence and weariness, as well as remarkable hyperpigmentation of the skin. Laboratory tests revealed adrenal insufficiency with a positive titer of anti-adrenal antibodies, which led to APS-2 diagnosis in the presented case. As the clinical outcome at the early onset of the APS-2 is not distinctive, the authors would like to emphasize the significance of screening methods, especially in patients with other hormone abnormalities, to protect them from the consequences of life-threatening disturbances.